Application Research of Integrated Prefabricated Module Computer Room Solution Based on Computer Communication. Issue 2 (May 2021) - Zhu, Lei; Chen, Li; Dong, Tianbo; Cui, Weihong; Yu, Shaofeng
Abstract: Modular machine room is to divide the whole machine room into several independent areas. The scale, power load and configuration of each area are customized according to the requirements [1]. A module is a single, independent, small data center. With the continuous expansion of business demand, independent modules are added, which can be combined flexibly to meet the different requirements of different customers for reliability level, power density and security level, so as to realize the purpose of rapid construction.